2007
DOI: 10.1007/s10295-007-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing acetate formation in E. coli fermentations

Abstract: Escherichia coli remains the best established production organisms in industrial biotechnology. However, during aerobic fermentation runs at high growth rates, considerable amounts of acetate are accumulated as by-product. This by-product has negative effects on growth and protein production. Over the last 20 years, substantial research efforts have been spent to reduce acetate accumulation during aerobic growth of E. coli on glucose. From the onset it was clear that this quest should not be a simple nor uncom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
149
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(156 citation statements)
references
References 104 publications
4
149
2
1
Order By: Relevance
“…During the fed-batch phase, the acetate was consumed and a plateau of about 1.2 g/L was reached with glucose, while it remained near zero with glycerol. According to De Mey et al (2007), the presence of acetate in concentrations above 1 g/L can be harmful to the cell growth and also to recombinant protein production. The comparison of these carbon sources has been reported by different authors (Martinez et al 2008;Hansen and Eriksen 2007), and they have also found a decrease of acetate formation using glycerol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the fed-batch phase, the acetate was consumed and a plateau of about 1.2 g/L was reached with glucose, while it remained near zero with glycerol. According to De Mey et al (2007), the presence of acetate in concentrations above 1 g/L can be harmful to the cell growth and also to recombinant protein production. The comparison of these carbon sources has been reported by different authors (Martinez et al 2008;Hansen and Eriksen 2007), and they have also found a decrease of acetate formation using glycerol.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on cultivation conditions, medium compositions, and genetic approaches have been used in order to minimize acetate formation (De Mey et al 2007). The use of different carbon sources such as glycerol has been shown to reduce acetate formation (Hansen and Eriksen 2007;Martinez et al 2008) and also improve the activity of the products (Hansen and Eriksen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of acetate is significant for cells cultured in a defined medium than a complex medium. Inhibitory effect of acetic acid on growth of E. coli cells affecting the volumetric productivity of recombinant proteins during high cell density fermentation has been widely documented 1,[26][27] . Acetate is produced when E. coli is grown under anaerobic or oxygen-limiting conditions; however, E. coli cultures growing in the presence of excess glucose can also produce acetate even under aerobic conditions.…”
Section: Accumulation Of Acetate During Fermentationmentioning
confidence: 99%
“…Exponential feeding is widely used so that the cells can be grown at the desired specific growth rate, preventing the formation of toxic byproducts like acetate [24][25][26][27] . The feeding method to maintain the desired specific growth rate is fairly simple and amenable to feed-forward control using substrate balance equations 28 .…”
mentioning
confidence: 99%
“…The latter strategies are based on the alteration of the central metabolism of E. coli. These strategies mainly target the glucose uptake mechanism, the acetate pathway and the pyruvate branch point (starting point to direct the carbon flow to acetate) [7,12,13,[16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%